Kesulitan Mahasiswa Calon Guru Matematika dalam Menentukan Basis dan Numerus Materi Logaritma - Kurniawan, Surya; Suhendra, Suhendra (Edumatica : Jurnal Pendidikan Matematika, 2022)
Logarithm has an important role in learning mathematics since various fields such as science, computer, finance, industry, and others are applied this material as one of the study subjects. In calculus, logarithm has an important role, especially natural logarithm. This study aims to determine pre-service mathematics teachers' difficulties in solving logarithm bases and numerus material. The subjects are students in the first semester in one university at Banda Aceh city who take elementary algebra course. The research was conducted with a descriptive approach to explain the difficulties that students faced, and it applied several steps such as providing logarithm test to students, determining the difficulties, and verifying it by interviewing students who had difficulties based on their answers. This study revealed that there were various difficulties that students faced such as; (1) lack of understanding of bases and numerus definitions of logarithms, (2) not being able to distinguish between expressions and logarithmic equations, (3) remembering too many formulas so that they do not understand the context of the problem, (4) couldn’t determine the position of irrational numbers on the number line.